PENGARUH BIAYA TERHADAP PENJUALAN - Helmiati Helmiati (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Sales are one of the important aspects in the continuity of company operations because success in increasing sales will determine the extent to which the company is able to grow and survive in market competition. The phenomenon of sales stagnation and fluctuation in automotive and component subsector companies is influenced by various factors from within the company, including production costs, promotional costs and distribution costs. This study aims to determine how the effect of production costs, promotional costs and distribution costs on sales. The sample in this study amounted to 12 automotive and component subsector companies listed on the IDX in 2022-2024 which were selected using purposive sampling technique. The data analysis method used in this study is multiple linear regression using the SPSS application. The results showed that there was a significant influence between production costs, promotional costs and distribution costs on sales.               Keywords: Production Cost, Promotional Cost, Distribution Cost, Sales.